Etnomedisin Tumbuhan Obat oleh Pengobat Tradisional di Negeri Saleman, Maluku Tengah - Abdul M Ukratalo (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Saleman Village is endowed with abundant natural resources that can be utilized by the local community, including various types of medicinal plants that grow either naturally or are intentionally cultivated by its inhabitants. Traditional medicine is an alternative treatment and an essential component of the public health system, passed down through generations. This study analyzes the ethnomedicinal knowledge of medicinal plants used by traditional Saleman Village, Central Maluku healers. A qualitative approach was employed, using in-depth interviews with five traditional healers. The collected data were then analyzed using qualitative descriptive methods. The results identified 36 types of medicinal plants from 26 families. The most commonly used plant part was the leaf (45%), with the predominant method of preparation being boiling (69.4%), and the primary mode of use was oral consumption (70.3%). The local knowledge of Saleman's people regarding the utilization of medicinal plants can serve as a foundation for more in-depth pharmacological research. By integrating modern research with local wisdom, the medicinal plants of Saleman Village hold the potential for development into more effective and safer herbal medicines for health.